Four rooted maxillary third molar: a case report of a rare clinical presentation - Babatunde O. Bamgbose; Mohammad A. Kaura; Anas I. Yahaya (Journal of Dentomaxillofacial Science, 2018)
Objective: Maxillary molars are known to have three roots (two buccal and one palatal) and the occurrence of four-rooted maxillary molars is uncommon. Maxillary teeth with accessory roots have been classified into four categories based on root configurations. The presence of an accessory root may complicate an otherwise routine exodontia of the maxillary third molar, especially because of the proximity of the floor of the maxillary antrum and the maxillary tuberosity.Methods: A 35 year old male patient was referred to the Oral Diagnostic Sciences Clinic from the Ear Nose and Throat (ENT) Clinic on account of right-sided facial pain of one-month duration. Intraoral examination, revealed a carious maxillary right third molar that was tender to percussion. Periapical radiograph revealed large coronal radiolucency involving the distal half of the tooth with extension into the distal pulp horn. The portrayed outlines of the roots showed two buccal roots and the outlines of what appears to be two straight palatal roots.Results: Socket extraction of the maxillary third molar under local anaesthesia.Conclusion: In clinical practice of endodontics and oral surgery, it is good practice to anticipate the likely presence of an accessory root on a maxillary molar in order to avoid post-operative complications following treatment.